2017
DOI: 10.3390/rs9070757
|View full text |Cite
|
Sign up to set email alerts
|

Ku-, X- and C-Band Microwave Backscatter Indices from Saline Snow Covers on Arctic First-Year Sea Ice

Abstract: Abstract:In this study, we inter-compared observed Ku-, X-and C-band microwave backscatter from saline 14 cm, 8 cm, and 4 cm snow covers on smooth first-year sea ice. A Ku-, X-and C-band surface-borne polarimetric microwave scatterometer system was used to measure fully-polarimetric backscatter from the three snow covers, near-coincident with corresponding in situ snow thermophysical measurements. The study investigated differences in co-polarized backscatter observations from the scatterometer system for all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…It may also be possible to combine Ku-and Ka-bands to simultaneously retrieve both ice thickness and snow depth during winter (Lawrence et al, 2018;Guerreiro et al, 2016). Other studies have additionally suggested the feasibility of combining CS2 with snow freeboard observations from laser altimetry (e.g., ICESat-2) to map pan-Arctic snow depth and ice thickness during the cold season (Kwok and Markus, 2018;Kwok et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It may also be possible to combine Ku-and Ka-bands to simultaneously retrieve both ice thickness and snow depth during winter (Lawrence et al, 2018;Guerreiro et al, 2016). Other studies have additionally suggested the feasibility of combining CS2 with snow freeboard observations from laser altimetry (e.g., ICESat-2) to map pan-Arctic snow depth and ice thickness during the cold season (Kwok and Markus, 2018;Kwok et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, several key uncertainties limit the accuracy of the radar-based freeboard retrieval, which then propagate into the freeboard-to-thickness conversion. One important uncertainty pertains to inconsistent knowledge on how far the radar signal penetrates into the overlying snow cover (Nandan et al, 2020;Willatt et al, 2011;. The general assumption is that the radar return primarily originates from the snow-sea ice interface at the and from the air-snow interface at the Ka-band (AltiKa).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous synthetic aperture radar (SAR) and surface-based scatterometer studies of snow-covered FYI have provided the geophysical basis for development of active microwave based snow on sea ice thickness retrievals [38][39][40][41][42][43][44]. These studies have shown that changes in snow temperature on FYI are manifest as changes in total σ • .…”
Section: Introductionmentioning
confidence: 99%
“…As applications devoted to snow monitoring, the co-pol. and dual-frequency ratios at Ku-, X-and C-bands were demonstrated to be adequately sensitive to variations in snow thickness for the Antarctic first year ice [21]. In [22], the combination of active and passive microwave acquisitions allowed characterizing the seasonal behavior of snow properties and retrieving the effective correlation length and the snow water equivalent.…”
mentioning
confidence: 99%